Decision Support System for Determining Outstanding Teachers Using the Simple Additive Weighting (SAW) Method: Sistem Pendukung Keputusan Penentuan Guru Berprestasi Dengan Menggunakan Metode Simple Additive Weighting (SAW) - kharisma kharisma; Wahyu Prima; Raimon Efendi (International Journal of Technology Vocational Education and Training, 2022)
In the world of education, the figure of a qualified educator is needed. The main task of the teacher is to teach, educate, guide, direct, train, assess, and evaluate students. In order to improve the quality of education, it is necessary to have a form of appreciation so that the quality of a teacher is even better. The form of appreciation for the teacher is applied by selecting outstanding teachers. The problem is that the selection process for outstanding teachers is still subjective. Because it is only based on the personal opinion of each teacher and is not based on certain criteria. The method used in this study is the Simple Additeve Weighting (SAW) method, often known as the weighted addition method. To avoid the subjectivity of the resulting decisions, a decision support system (DSS) is needed that can help assess teacher performance in deciding to become an outstanding teacher.